2010
DOI: 10.4061/2010/957645
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine Is a Risk Factor in Predialysis Patients When Associated with Malnutrition and Inflammation

Abstract: The increased level of plasma total homocysteine (tHcy) in chronic kidney disease patients has been reported as a new and independent risk factor for cardiovascular disease. However, after the description of reverse epidemiology in the renal population, the association of tHcy and nutrition became less clear. We evaluated the association between homocysteine, nutritional status, and inflammation, and their impact on mortality in 95 predialysis patients. High sensitivity C-Reactive Protein (hs-CRP), interleukin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…There are also parallel changes in plasma creatinine, suggesting a renal component. This is consistent with the mild increases (up to about 30 μmol/L) found with renal dysfunction 14. Mild increases in plasma total homocysteine may also occur with lifestyle factors including heavy coffee and tea consumption, smoking and lack of exercise.…”
Section: Acquired Causes Of Hhcsupporting
confidence: 83%
“…There are also parallel changes in plasma creatinine, suggesting a renal component. This is consistent with the mild increases (up to about 30 μmol/L) found with renal dysfunction 14. Mild increases in plasma total homocysteine may also occur with lifestyle factors including heavy coffee and tea consumption, smoking and lack of exercise.…”
Section: Acquired Causes Of Hhcsupporting
confidence: 83%
“…Although the mechanisms by which homocysteine induce vascular injury are not yet completely unraveled, homocysteine has been reported to induce oxidative stress, inhibit antioxidant enzymes, accelerate endothelial dysfunction, and so on [3,4]. Consistently, previous observations have shown that hyper-homocysteinemia is an independent risk factor for atherosclerotic vascular disease in patients with end-stage renal disease (ESRD) [5,6,7]. Folic acid (FA) supplements reduce serum homocysteine levels and improve endothelial dysfunction [8,9], thereby initiating a hypothesis that FA supplements may have a positive impact on clinical outcomes in patients with chronic kidney disease (CKD).…”
Section: Introductionsupporting
confidence: 60%
“…[8][9][10][11][12] Furthermore, an advantage of this study compared with others is that it is a multicenter study consisting entirely of incident patients. [8][9][10][11][12] Therefore, the results of this analysis can be generalized to CKD patients starting with a regular program of predialysis care.…”
Section: Discussionmentioning
confidence: 97%
“…Studies performed in this specific population show a prevalence of moderate malnutrition of 19.6% to 28.9%, whereas in these studies, severely malnourishment was very rare. [8][9][10][11][12] It has to be noted that only a few small studies, the biggest consisting of 95 patients, have been performed including a mixture of incident and prevalent predialysis patients. [8][9][10][11][12] Different tools for assessing nutritional status have been used in these studies.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation